Photocatalytic performance of heterojunction S-Tyr-NDI-Tyr/TiO2 formed by self-assembled naphthalimide derivatives and titanium dioxide. (June 2022) - Liu, Di; Chen, Yunning; Guan, Renquan; Zhao, Jie; Jin, Huimin; Zhang, Siyi; Shang, Qingkun
Abstract: In this paper, a type of heterojunction photocatalyst S-Tyr-NDI-Tyr/TiO2 was prepared by self-assembly of tyrosine-substituted naphthamide (NDA) and bonding with titanium dioxide. The self-assembly process and driving force of monomer M-Tyr-NDI-Tyr were simulated by theoretical calculation. Taking atenolol as the target pollutant, the photocatalytic performance of the heterojunction photocatalyst under visible light was studied, and the degradation products were analyzed by mass spectrometry. The environmental toxicity of photocatalytic process was evaluated by luminescent bacteria. The principle of high photocatalytic activity of S-Tyr-NDI-Tyr/TiO2 heterojunction photocatalyst was proposed by analyzing the fluorescence spectrum, photocurrent density and resistance, electron paramagnetic resonance spectrum, free radical capture experiment and energy band position of S-Tyr-NDI-Tyr/TiO2 heterojunction photocatalyst. In addition, the photocatalytic degradation of different pollutants by S-Tyr-NDI-Tyr/TiO2 heterojunction photocatalyst was also studied. This work will provide a useful example for the further development of new and efficient organic supramolecular/inorganic semiconductor composite photocatalysts. Graphical abstract: Image 1 Highlights: Tyrosine substitution and self-assembly to obtain H-type supramolecule S-Tyr-NDI-Tyr. Constructed a heterojunction S-Tyr-NDI-Tyr/TiO2 with high photocatalytic activity. Pollutants such as atenolol are quickly degraded and mineralized by heterojunction. Analyzed the degradation path of pollutants and environmental toxicity in detail.